Law as an Art in the Era of Digital Disruption: A Humanistic-Progressive Approach - Hyronimus Rhiti (Rechtsvinding, 2026)
This study situates law within the accelerating context of digital disruption, where technologies such as artificial intelligence, blockchain, and automated decision-making challenge the rigidity of traditional legal paradigms and call for more adaptive and human-centered approaches. The purpose of this study is to reconstruct the paradigm of Indonesian law by conceptualizing law as an art, emphasizing flexibility, interpretative sensitivity, and responsiveness to social change through a humanistic-progressive approach. Employing a normative juridical method combined with conceptual and philosophical analysis, this research draws upon statutory regulations, legal doctrines, and interdisciplinary perspectives, particularly progressive legal theory and humanistic jurisprudence, to examine the limitations of positivistic frameworks in addressing digital-era complexities. The findings reveal that the current legal system tends to be formalistic and reactive, resulting in gaps when confronted with rapidly evolving digital phenomena, such as smart contracts, digital assets, and algorithmic governance. In contrast, positioning law as an art enables a more contextual, value-oriented, and justice-driven interpretation, allowing legal actors to balance certainty with fairness and societal needs. This approach also reinforces the role of judges and policymakers as active interpreters rather than mere enforcers of static norms. The study concludes that a humanistic-progressive reconstruction of law is essential to ensure its relevance and effectiveness in the digital era, advocating for a paradigm shift that integrates ethical considerations, social realities, and technological advancements into the development and application of law in Indonesia.